El simulador stock trader en la enseñanza aprendizaje del funcionamiento del mercado de valores en los estudiantes de la Universidad Técnica de Cotopaxi, de la carrera de ingeniería comercial en el período 2012 - 2013 - Bocancho Quingaluisa, Fabricio Rigoberto (2015)
The following research was performed at Cotopaxi Technical University of, Commercial Engineering, whose main objective was based in designing a simulator operating manual Stock Trader which will be an important guide for both the teacher and the student in the process and analysis of market research. The main problem was that both teachers and students of the race did not use technology tools which help them minimize their resources and thus be able to develop skills in conducting a market research….